Dental caries experience and use of dental services among preschool children in Ajman, UAE - R. HASHIM, W. M. THOMSON, K. M. S. AYERS, J. D. LEWSEY, & M. AWAD (Paediatric Dentistry, 2006)
The aim of this study was to estimate the prevalence and severity of dental caries in the primary dentition of young children in Ajman, UAE, and investigate its association with sociodemographic characteristics and use of dental services.